ANALISIS KONSEP THEORY OF PLANNED BEHAVIOR TERHADAP PEMBELAJARAN WIRAUSAHA DAN PENDIDIKAN EKONOMI KELUARGA PELAKU UMKM - Syamsuri Syamsuri (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2019)
Research about analysis concept theory of planned behavior towards entrepreneurship learning and economic family education for UMKM people in Pontianak city has been conducted. The aim of the research is to analyze of application the variables in theory ofPlanned behavior to entrepreneurship learning and economic family education for UMKM people in Pontianak city and to analyze the partial and simultant influence of the application of variables in the Theory of Planned Behavior concept. The research method is a survey, non-experimental, and is a correlational study. Population in this study were people UMKM in Pontianak City who had attended entrepreneurship learning by the local government amounted to 418, the sample fixed as 204 by using the Slovin formula. The data were analysis by description and regression using SPSS programs. Result showed the variables in Theory of Planned Behavior concept in their application to UMKM people in Pontianak all in quite good categories. The variables in Theory of Planned Behavior consisting of Attitudes, Subjective Norms, Perceived Behavioral Control, and Behavioral Intensions partially and simultant have a significant effect on entrepreneurship learning and Economic family Education to UMKM people in Pontianak City.